Quality ume clones post-harvest in cultivated Jundiai - SP, Brazil - Vieites, Rogerio Lopes [UNESP]; Fujita, Erika [UNESP]; Mendonca, Veridiana Zocoler de [UNESP]; Furlaneto, Karina Aparecida [UNESP]; Caetano, Priscilla Karin [UNESP]; Ramos, Juliana Arruda [UNESP]; Daiuto, Erica Regina [UNESP] (Univ Federal Mato Grosso, 2016)
The ume is a fruit little known Brazilians, but widely consumed in Asian countries. There are several clones of this fruit that may have different post-harvest characteristics, so the aim of this study was to evaluate the diversity of ume clones as postharvest attributes. We evaluated five ume clones named 3, 6, 13, 15 and XVII, originating in the Instituto Agronomico de Campinas (IAC), in Jundiai (SP). The fruits of each clone were packed in coated PVC trays with plastic films stored under refrigeration (8 +/- 1 degrees C and 85 +/- 5% RH) for 21 days, and collected three samples of 21 fruits of each clone and evaluated for loss mass, pulp yield, respiratory rate, soluble solids, titratable acidity, pH and ascorbic acid. The design was completely randomized in a factorial design, followed by the Tukey test at 5% significance level. It was found that fruits of different clones showed low weight loss of less than 1.5% pulp yield and high, exceeding 65%. Clone 3 had lower respiratory activity, the clone 6 lower acidity values, clones 13 and XVII higher soluble solids and the 15 largest clone ascorbic acid content.
Keywords: Prunus mume; physical-chemistry; refrigerate storage; genetic diversity